The value of indicators for the teaching-learning process and educational inspection - Alonso de Castro, María Goretti (Avances en Supervisión Educativa, 2024)
This article explores the value of educational indicators in the teaching-learning process and their application in educational inspection. Indicators from the “2024 State System of Education Indicators” and “Education at a Glance 2024” are essential for evaluating academic performance, equity, and the quality of the education system. Through a documentary analysis based on reports and national and international databases, key indicators are examined that track educational progress and institutional quality. The findings show that indicators help identify problems in teaching, evaluate teacher performance, ensure regulatory compliance, and promote equity in access to education. Furthermore, educational inspection relies on these indicators to improve school management and ensure accountability. Challenges related to data collection and proper use are also mentioned, especially in socioeconomically diverse contexts.